2020
DOI: 10.3390/cells9112361
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome Biogenesis Alterations in Colorectal Cancer

Abstract: Many studies have focused on understanding the regulation and functions of aberrant protein synthesis in colorectal cancer (CRC), leaving the ribosome, its main effector, relatively underappreciated in CRC. The production of functional ribosomes is initiated in the nucleolus, requires coordinated ribosomal RNA (rRNA) processing and ribosomal protein (RP) assembly, and is frequently hyperactivated to support the needs in protein synthesis essential to withstand unremitting cancer cell growth. This elevated ribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 196 publications
(356 reference statements)
1
30
0
Order By: Relevance
“…A distinctive feature of cancer cells is the constitutive activation of growth factor signalling pathways that alter the activity of transcription factors [33,34] responsible for the increased ribosome biogenesis due to the hyperactivation of RNA polymerases I and III [35,36]. Different reports have highlighted that ribosome biogenesis has a role in the initial phases of CRC tumour progression, mainly due to rRNA polymerase (or its cofactors) overexpression or mutation [37,38]. Another study [39] demonstrated that a germline mutation in RPS20, encoding a component of the small ribosomal subunit, increases the predisposition to develop a particular form of hereditary CRC named familial colorectal cancer type X (FCCX).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A distinctive feature of cancer cells is the constitutive activation of growth factor signalling pathways that alter the activity of transcription factors [33,34] responsible for the increased ribosome biogenesis due to the hyperactivation of RNA polymerases I and III [35,36]. Different reports have highlighted that ribosome biogenesis has a role in the initial phases of CRC tumour progression, mainly due to rRNA polymerase (or its cofactors) overexpression or mutation [37,38]. Another study [39] demonstrated that a germline mutation in RPS20, encoding a component of the small ribosomal subunit, increases the predisposition to develop a particular form of hereditary CRC named familial colorectal cancer type X (FCCX).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that tumour cells, being characterised by enhanced growth, might also have increased ribosome production associated with altered biogenesis and nucleolar modifications (in either number, shape, or size) [37]. Moreover, the mounting evidence highlights the strong links between rRNA synthesis and rProteins with the development of human cancers [38].…”
Section: Discussionmentioning
confidence: 99%
“…The top 40 hub genes detected from colorectal carcinoma (G3) datasets were found to be related to ribosome biogenesis in eukaryotes, rRNA processing, and pyrimidine and purine metabolism pathways. Previous studies have shown that the ribosome biogenesis pathway is altered in CRC, and the alterations lead to increased production of ribosomes linked to the initiation and progression of colorectal carcinogenesis [75]. Stedman et al (2015) showed that the dysfunction of ribosome biogenesis might also lead to p53-mediated apoptosis in some cancers [76].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the downregulated genes belong to the pathways of ribosome biogenesis, RNA transport, RNA degradation, and protein synthesis in endoplasmic reticulum. Ribosome biogenesis is hyperactivated in cancer cells to fulfill the increased demand of protein synthesis for sustaining an infinite growth potential [Slimane et al, 2020]. Downregulation of ribosome biogenesis in RecQL4-suppressed glioblastoma cells suggests that RecQL4 contributes to enhanced ribosome biogenesis.…”
Section: Recql4 Protects Cancer Cells From Endogenous and Exogenous Dna Damagementioning
confidence: 99%